Pola Pembinaan Keluarga Harmonis di Desa Binaan - Huldia Syamsiar; Khairul Rizal (Universitas Hamzanwadi, 2017)
The purpose of this study was to be able to find out how the form of harmonious family formation patterns in the village of Pesanggrahan, Montong Gading District. The method in this study is a qualitative research method with a descriptive approach. Informants in the study used Purposive Sampling methods by using Purposive Sampling. Based on the research conducted, it was obtained the result that the Harmonious family development program was a program proposed by the village community and fully supported by the Pesanggrahan village government, the hard work of the village government in the structured guidance in all aspects in each formation was able to present a harmonious family in the village of Pesanggrahan, there is an impression of the success of the Persanggrahan village government in managing the social structure of the local community. This is evidenced by the many awards received by Pesanggrahan Village thanks to the formation and condition of the community who can participate maximally in every village government program through entrepreneurship development activities, rotating lessons in each Kadus in Pesanggrahan Village and education for newly married good families and those who have long been married about family life with good and true through BKB (Bina Keluarga Balita), BKR (Bina Keluarga Remaja), and BKL (Bina Keluarga Lansia)